Capital Structure Construct and Family Control as Stimulus on Family Business Performance: Evidence From Indonesia - Yulianty, Puspa Dewi; Amani, Akbar Riskal; Purnomo, Budi; Purnamasari, Imas (Universitas Muhammadiyah Semarang, 2024)
The aim of this study is to find out and reproduce how the decision-making process of the capital structure in a family-owned company, and how the family control task serves as a kind of mediation in order to improve the business performance of the company. The target population of this research is the entire family company especially SMEs that is located in Bandung, whose company age is 1 to more than 30 years. Sampling techniques using probability techniques. The total respondents used were 140 respondents who were CEOs or directors and representatives of the family business. The analysis used is using track analysis using Partial Least Square (PLS) The findings of this study show that the process of improving the business performance of a family company is heavily influenced by the accuracy of decision-making in the capital structure and control of the family members themselves.